China Merchants Bank in transition - Mao, Chuanjiang, (SAGE knowledge. Cases., 2016)
'When I recall the past 10 years working for China Merchants Bank, I keep thinking about how fast the bank has grown and the early advantages we had thanks to our leading position in IT. Things change. Other major banks' underwent stockholding reform, improved corporate governance and IPOS, becoming more vigorous and competitive than before. Our old IT capacity was no longer our advantage. Banks are now also challenged by direct capital market and third-party payment platform. Only by self-disruption can we build up new strength and only by differentiating ourselves from other banks can we fight for our survival and find our unique way to success,' said Ma Weihua, the 60 year old CEO of China Merchants Bank, in 2009. This case study discusses this issue.